Proceedings of the 1st South Borneo International Conference on Sport Science and Education (SBICSSE 2019) 2020
DOI: 10.2991/assehr.k.200219.005
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Challenges to Using Technology in Physical Education

Abstract: This survey research aims to explore the challenges of using technology in Physical Education. The data was taken through a survey using an open-ended questionnaire that has been distributed through Google forms which were distributed over two months and five days. The population is 49 Physical Education teachers in West Java. The population consisted of 13 Physical Education teachers from Cimahi, 9 from Bandung, 11 from Batujajar, 8 from Garut and 8 from Purwakarta. The total Sampling was used in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Several studies have confirmed that PE teachers are still experiencing problems in utilizing information technology (Friskawati et al, 2019;Irwahand et al, 2022). Therefore, the latest study by recommended that teachers improve the quality of learning by integrating information technology (Blegur, Lumba, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that PE teachers are still experiencing problems in utilizing information technology (Friskawati et al, 2019;Irwahand et al, 2022). Therefore, the latest study by recommended that teachers improve the quality of learning by integrating information technology (Blegur, Lumba, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This issue is compounded by the difficulties teachers face in incorporating digital tools into their pedagogy and adapting to rapidly evolving technological landscapes. Friskawati et al (2020) and Pohrebniak et al (2022) further explored these challenges, noting that the successful integration of technology requires not only access to resources but also a shift in teaching methodologies and continuous professional development.…”
Section: Previous Studiesmentioning
confidence: 99%